Effect of exercise induced hypoxaemia on myocardial repolarisation in severe chronic obstructive pulmonary disease - Smith, R. (BMJ Group, 1998)
BACKGROUND—Exercise training is being promoted increasingly for patients with chronic obstructive pulmonary disease (COPD). Many of these patients experience exercise related arterial desaturation but the clinical importance of these hypoxaemic episodes is not known. QTc dispersion is a marker of myocardial repolarisation abnormalities and there has been much interest in its role as a non-invasive predictor of cardiac arrhythmias and sudden death. However, little is known about the dynamic effects that exercise and hypoxaemia have on QTc dispersion in patients with COPD. METHODS—20 patients with severe COPD (FEV(1) <40% predicted) undertook two 15 minute treadmill tests at a speed calculated to produce a constant workload of 50% maximum oxygen consumption (VO(2)max) during which they were blindly given either air or 35% oxygen in random order. Physiological measurements taken throughout exercise included 12 lead electrocardiograms from which QTc dispersion values were calculated according to standard criteria. Nine of the patients who desaturated with exercise were studied further. A similar degree of hypoxaemia was induced at rest by giving them a titrated mixture of air and oxygen and the changes in QTc dispersion were recorded. RESULTS—11 of the 20 patients developed significant hypoxaemia (desaturation by ⩾5% to <90%) with exercise breathing air. There were no significant changes in QTc dispersion with either exercise or hypoxaemia. There were no significant changes in QTc dispersion when comparing those who did and did not desaturate, and those with and without a high baseline QTc dispersion values (60 ms). Induced hypoxaemia without exercise also failed to worsen QTc dispersion. CONCLUSIONS—No evidence was found to suggest that exercise, even when associated with hypoxaemia, causes myocardial repolarisation abnormalities in patients with COPD.